Comparing Hearing Outcomes in Irradiated and Conservatively Managed Vestibular Schwannoma. Issue 3 (March 2022) - Ismail, Omneya; Sobhy, Ossama; Assal, Samir; Sanghera, Paul; Begg, Philip; Irving, Richard
Abstract : Objective: Compare hearing outcome for vestibular schwannoma patients following stereotactic radiosurgery (SRS) or conservative management. Study Design: Retrospective review. Setting: University Hospital. Patients: Patients with small- or medium-sized sporadic vestibular schwannoma (intracanalicular or with CPA component <2 cm) who were managed conservatively or underwent SRS with available clinical, radiological, and audiometric data from the time of presentation (or just before radiotherapy for the SRS group) and most recent follow-up; with the two sets of data to be compared being at least 3 years apart (minimum follow-up period). Interventions: SRS or observation. Main Outcome Measure: Pure-tone averages, speech discrimination scores, and corresponding hearing classifications. Results: Two hundred forty-seven patients met our inclusion criteria; 140 were managed conservatively with a mean follow-up period of 5.9 ± 1.6 years and 107 underwent SRS with a mean follow-up period of 7.1 ± 1.9 years. There was significant deterioration of hearing measures for both groups; with the SRS group displaying consistently worse measures. SRS patients showed worse mean pure-tone averages and speech discrimination scores decline rates by 2.72 dB/yr and 2.98 %/yr, respectively, when compared with conservatively managed patients. Stratifying patients according to Tokyo's hearing classification revealed that 68.75% of conservatively managed patients who had baseline serviceable hearing preserved their hearing throughout the studied period compared with only 15.38% of the SRS patients. Conclusion: Based on our data we conclude that patients with small- and medium-sized tumors will have a better hearing outcome if managed via an initial conservative approach with radiotherapy reserved for those demonstrating disease progression.